Surgical Outcomes Following Repeat Transsphenoidal Surgery for Nonfunctional Pituitary Adenomas: A Retrospective Comparative Study. Issue 2 (15th May 2018) - Bakhsheshian, Joshua; Wheeler, Sarah; Strickland, Ben A; Pham, Martin H; Rennert, Robert C; Carmichael, John; Weiss, Martin; Zada, Gabriel
Abstract: BACKGROUND: Endonasal transsphenoidal surgery (ETSS) remains the preferred treatment for recurrent or residual nonfunctional pituitary adenomas (NFPAs). However, surgical complications and outcomes with repeat ETSS are unclear. OBJECTIVE: To compare outcomes from primary and repeat ETSS in patients with NFPAs. METHODS: Retrospective review of ETSS for NFPAs at USC University Hospital and LAC + USC Medical Center between 2000 and 2015. Patients with ≥3-mo follow-up data were included. Patients were categorized as primary or repeat ETSS. Patient and tumor characteristics were compared preoperatively, and postoperative outcomes were analyzed. RESULTS: Two hundred sixty-eight patients (89%) met the inclusion criteria (primary ETSS = 211 and repeat ETSS = 57) with a mean follow-up time of 38 mo (range 3-235 mo). Both groups had similar demographics, endocrine function, and tumor characteristics. Surgical complication rates were similar and no mortalities were observed. Repeat ETSS patients had a higher rate of new postoperative panhypopituitarism (primary ETSS: 0.5% vs repeat ETSS: 7.1%, P = .011), lower rates of gross total resection (GTR; primary ETSS: 59.2% vs repeat ETSS: 26.3%, P = .001), and greater rates of postoperative radiosurgery (36.8% vs 24.2%, P = .009). At 2-yr follow-up, progression-free survival on MRI was similar in both groups (primary ETSS: 97.9% vs repeat ETSS: 95.4%, log-rank test P = .807). CONCLUSION: At experienced tertiary pituitary centers, repeat ETSS for NFPAs was associated with a similar incidence of surgical complications as primary ETSS. However, repeat ETSS carried a higher rate for worsening endocrine dysfunction and a lower rate of GTR.